PROFIL PENGGUNAAN VITAMIN DAN SUPLEMEN PADA PASIEN COVID-19 RAWAT INAP DI RUMAH SAKIT BHAYANGKARA TK. III BANJARMASIN PADA TAHUN 2020 - Muliyani Muliyani; Muhammad Zaini; Nazhipah Isnani; Maulida Rahmah (Jurnal Insan Farmasi Indonesia, 2022)
This study is conducted to determine the characteristics of covid-19 patients and the profile of the use of vitamins and supplements in hospitalized covid-19 patients during the pandemic at Bhayangkara Hospital Level III Banjarmasin. The purpose of this study is determine the profile of the use of vitamins and supplements in hospitalized Covid-19 patients at Bhayangkara Hospital Level III Banjarmasin in 2020. The source of data in this study is secondary data taken from the results of medical records in 2020. The results of the research conducted were that the percentage of male patients infected with Covid- 19 was more than 69 people (71%) and the age group above 30 years was 76 people (78.35%). While the occupation is the police with a total of 48 people (49%). While the percentage of use of vitamins and supplements in Covid-19 patients hospitalized at Bhayankara Hospital Banjarmasin in 2020 is Vitamin D (61%), and Vitamin C (39%). As for supplements, namely Curcuma (63%), Becom C (26%), Imboost Force syrup (4%), Hepa-Q (2%), Cibexon syrup (1%), Becom zet (2%), Curvit (2 %) and Curbexon syrup (1%), in 97 samples.